A cross-cultural comparison of the processes underlying the associations between sharing of and exposure to alcohol references and drinking intentions - Geusens, Femke and Bigman-Galimore, Cabral A and Beullens, Kathleen (New Media & Society, 2020)
This study is among the first to cross-culturally compare the associations between social media use and emerging adults’ drinking behavior in an accepting (Belgium) and comparatively restricted (USA) Western drinking culture. A cross-sectional survey was administered among 770 college students ( n USA = 253, 24% male; n Belgium = 487, 34% male) aged 18–20 years. Structural equation modeling was used and demonstrated that the association between exposure to others’ alcohol-related content on social media and drinking intentions operated similarly via more positive descriptive and injunctive norms for both populations, whereas the association between self-sharing and drinking intentions operated similarly via more positive attitudes. However, only among Belgian students was sharing alcohol references also related to drinking intentions through descriptive norms. Overall, this study points to the generalizability of attitudes and social norms as mechanisms of alcohol-related social media (self-)effects among emerging adult college students across Western drinking cultures.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDYxNDQ0ODE5ODYwMDU3